Republic of Congo : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Nonobservance of Performance Criteria, Rephasing, and Extension of Arrangement-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2006)
The completion of the Second Review Under the Poverty Reduction Growth Facility Arrangement was delayed to address important governance and transparency concerns. Macroeconomic performance was strong in the year 2005. Policy discussions focused on improving macroeconomic management against the background of continued high oil prices and efforts to further strengthen governance. The medium-term economic outlook is more favorable than expected, owing to higher oil price projections. The main objective of the fiscal policy is to strengthen the public sector balance sheet.